An overview on NMR spectroscopy based metabolomics - Nalini Kanta Sahoo; G Tejaswini; Madhusmita Sahu; KS Muralikrishna (International Journal of Pharmaceutical Sciences and Developmental Research - Peertechz Publications, 2020)
Introduction: A field of bioscience analysis that uses High throughput (HT) technologies to identify the products of metabolism formed in the cell metabolic processes (i.e. the metabolome). This process is termed metabolomics.The first NMR based metabolic studies were carried out by Wilson and Burlingame in the year 1974. Nuclear magnetic spectroscopy is one technique using which one can identify and characterize the metabolites formed due to metabolism. Methodology: The NMR workflow is as follows: Sample preparation  sample loading and spectral acquisition  spectral processing  Spectral deconvolution data interpretation. Conclusion: In the upcoming years, it is expected that more works will be reported depending upon the advantages and strengths that the NMR spectroscopy offers with regard to metabolomics. The NMR spectroscopy technique offers high versatility, and specificity with respect to spectra. This technique will gain high potential in the future because of its reproducibility and the ability to quantify the metabolites.